# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime } = \sqrt {x +y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\tan \left (y\right )}{x -1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{{2}/{5}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x \left (y-1\right )^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x \left (y-1\right )^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 x \left (y-1\right )^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y+x \,{\mathrm e}^{-\frac {y}{x}}}{x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}+x y-x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}+x y-x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = y^{2}
\] |
✓ |
✓ |
|
\[
{}7 x y^{\prime }-2 y = -\frac {x^{2}}{y^{6}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 y = 2 \,{\mathrm e}^{\frac {1}{x}} \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+2 x y = \frac {1}{\left (x^{2}+1\right ) y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y = x^{3} y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {\left (1+x \right ) y}{3 x} = y^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-x y = x y^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{4} x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 y = 2 \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-4 y = \frac {48 x}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = x \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y}{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y+y^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{3} y^{\prime } = y^{4}+x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}+\sec \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}+x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = 2 y^{2}+x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y^{2}+x^{2} {\mathrm e}^{-\frac {y^{2}}{x^{2}}}}{2 x y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y+y^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{3}+x^{3}}{x y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime }+x^{2}+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}-3 x y-5 x^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 2 x^{2}+y^{2}+4 x y
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = 3 x^{2}+4 y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y}{x -y}
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right ) \left (\ln \left (y\right )-\ln \left (x \right )\right ) = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{3}+2 x y^{2}+x^{2} y+x^{3}}{x \left (x +y\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +2 y}{y+2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{y-2 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x y^{2}+2 y^{3}}{x^{3}+x^{2} y+x y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x^{3}+x^{2} y+3 y^{3}}{x^{3}+3 x y^{2}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}+x y-4 x^{2}
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = x^{2}-x y+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y^{2}-x y+2 x^{2}}{x y+2 x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}+x y+x^{2}}{x y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-6 x +y-3}{2 x -y-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x +y+1}{x +2 y-4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {-x +3 y-14}{x +y-2}
\] |
✓ |
✓ |
|
\[
{}3 y^{2} y^{\prime } x = y^{3}+x
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = 3 x^{6}+6 y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{3} y^{\prime } = 2 y^{2}+2 x^{2} y-2 x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = y^{2} {\mathrm e}^{-x}+4 y+2 \,{\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y^{2}+\tan \left (x \right ) y+\tan \left (x \right )^{2}}{\sin \left (x \right )^{2}}
\] |
✓ |
✓ |
|
\[
{}x \ln \left (x \right )^{2} y^{\prime } = -4 \ln \left (x \right )^{2}+y \ln \left (x \right )+y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x \left (y+2 \sqrt {x}\right ) y^{\prime } = \left (y+\sqrt {x}\right )^{2}
\] |
✓ |
✓ |
|
\[
{}\left (y+{\mathrm e}^{x^{2}}\right ) y^{\prime } = 2 x \left (y^{2}+y \,{\mathrm e}^{x^{2}}+{\mathrm e}^{2 x^{2}}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{x} = \frac {3 x^{2} y^{2}+6 x y+2}{x^{2} \left (2 x y+3\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {3 y}{x} = \frac {3 y^{2} x^{4}+10 x^{2} y+6}{x^{3} \left (2 x^{2} y+5\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 1+x -\left (2 x +1\right ) y+x y^{2}
\] |
✓ |
✓ |
|
\[
{}6 x^{2} y^{2}+4 x^{3} y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y \cos \left (x \right )+4 x \,{\mathrm e}^{x}+2 x^{3} y+\left (3 \sin \left (x \right )+3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}14 x^{2} y^{3}+21 y^{2} y^{\prime } x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}2 x -2 y^{2}+\left (12 y^{2}-4 x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2}+\left (x +y\right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 x +7 y+\left (4 y+3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-2 y^{2} \sin \left (x \right )+3 y^{3}-2 x +\left (4 y \cos \left (x \right )+9 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +y+\left (2 y+2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2}+2 x y+4 y^{2}+\left (x^{2}+8 x y+18 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2}+8 x y+y^{2}+\left (2 x^{2}+\frac {x y^{3}}{3}\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}\frac {1}{x}+2 x +\left (\frac {1}{y}+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \sin \left (x y\right )+x y^{2} \cos \left (x y\right )+\left (x \sin \left (x y\right )+x y^{2} \cos \left (x y\right )\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}\frac {x}{\left (x^{2}+y^{2}\right )^{{3}/{2}}}+\frac {y y^{\prime }}{\left (x^{2}+y^{2}\right )^{{3}/{2}}} = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \left (x^{2} y^{2}+2 x y^{2}\right )+6 x +\left (2 x^{2} y \,{\mathrm e}^{x}+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} {\mathrm e}^{x^{2}+y} \left (2 x^{2}+3\right )+4 x +\left (x^{3} {\mathrm e}^{x^{2}+y}-12 y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x y} \left (x^{4} y+4 x^{3}\right )+3 y+\left (x^{5} {\mathrm e}^{x y}+3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} \cos \left (x \right ) y-x^{3} y \sin \left (x \right )+4 x +\left (8 y-x^{4} \sin \left (x \right ) y\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}4 y^{2} x^{3}-6 x^{2} y-2 x -3+\left (2 x^{4} y-2 x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-4 y \cos \left (x \right )+4 \sin \left (x \right ) \cos \left (x \right )+\sec \left (x \right )^{2}+\left (4 y-4 \sin \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y^{3}-1\right ) {\mathrm e}^{x}+3 y^{2} \left (1+{\mathrm e}^{x}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right )-y \sin \left (x \right )-2 \cos \left (x \right )+\cos \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x -1\right ) \left (y-1\right )+\left (x +2\right ) \left (x -3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}7 x +4 y+\left (4 x +3 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \left (y^{2} x^{4}+4 y^{2} x^{3}+1\right )+\left (2 x^{4} y \,{\mathrm e}^{x}+2 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{4} x^{3}+x +\left (y^{3} x^{4}+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2}+2 y+\left (2 y+2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{4} x^{3}+2 x +\left (y^{3} x^{4}+3 y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{x} = -\frac {2 x y}{x^{2}+2 x^{2} y+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {3 y}{x} = \frac {2 x^{4} \left (4 x^{3}-3 y\right )}{3 x^{5}+3 x^{3}+2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = -\frac {{\mathrm e}^{-x^{2}} \left (3 x +2 y \,{\mathrm e}^{x^{2}}\right )}{2 x +3 y \,{\mathrm e}^{x^{2}}}
\] |
✓ |
✓ |
|
\[
{}y+\left (2 x +\frac {1}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-y^{2}+x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}3 x^{2} y+2 x^{3} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{3}+3 y^{\prime } y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}5 x y+2 y+5+2 x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y+x +2 y+1+\left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}27 x y^{2}+8 y^{3}+\left (18 x^{2} y+12 x y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|